Cajal’s hypothetical mapping of the neurological forest through histology drawings - Ariso, Jose Maria (Research and Humanities in Medical Education, 2017)
One of the most significant steps taken to further the intimacy between medicine and art was taken by Santiago Ramón y Cajal, who was subsequently regarded as the father of modern neuroscience. In the late 19th century, Cajal started to draw neural tissues, and neurons in detail. As paradoxical as it may seem, the aesthetic quality of his drawings was so substantial that, in principle, they were not taken seriously by most of Cajal’s professional colleagues. However, they were eventually proven wrong, and today Cajal’s sketches are known for their brilliant clarity and accuracy. Indeed, in this article I provide a brief account of the scientific, aesthetic and even ethical relevance of Cajal’s work, which ended up holding pride of place in the history of medicine.